2000
DOI: 10.1289/ehp.00108983
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and assessment of the effects of mixtures of four xenoestrogens.

Abstract: The assessment of mixture effects of estrogenic agents is regarded as an issue of high priority by many governmental agencies and expert decision-making bodies all over the world. However, the few mixture studies published so far have suffered from conceptual and experimental problems and are considered to be inconclusive. Here, we report the results of assessments of two-, three- and four-component mixtures of o,p'-DDT, genistein, 4-nonylphenol, and 4-n-octylphenol, all compounds with well-documented estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(70 citation statements)
references
References 21 publications
4
66
0
Order By: Relevance
“…The E 2 was employed as a positive control and yielded a maximal absorbance at 10 9 mol L 1 with an EC 50 of 10 10.1 mol L 1 (data not shown), which was consistent with previous observation [28]. Enantioselective estrogenic activity was popular at this testing system for each SPs and their isomers, albeit only the stereo-structure was asymmetric among them.…”
Section: Enantioselectivity Of -Galactosidase Expression Modulation supporting
confidence: 88%
“…The E 2 was employed as a positive control and yielded a maximal absorbance at 10 9 mol L 1 with an EC 50 of 10 10.1 mol L 1 (data not shown), which was consistent with previous observation [28]. Enantioselective estrogenic activity was popular at this testing system for each SPs and their isomers, albeit only the stereo-structure was asymmetric among them.…”
Section: Enantioselectivity Of -Galactosidase Expression Modulation supporting
confidence: 88%
“…However, sensitivity of the 2P-YES in terms of EC50 values for estrogens seems to be lower. While we found a mean value of 2.35 nmol/L, typical EC50 data of E2 published for the original YES range from 0.13 to 0.4 nmol/L (Beresford et al 2000;Payne et al 2000;Rajapakse et al 2001;Miller et al 2001;Schultis and Metzger 2004). Variability behind these values may be high, as De Boever et al (2001) reported a 95% confidence interval of one order of magnitude (0.14-1.1 nmol/L).…”
Section: Performance Of the Modified Assay Protocolmentioning
confidence: 44%
“…Based on the complete concentration-response curves of the single agents, the overall effect of each mixture with defined composition was predicted applying both CA and IA models, as described in Payne et al (2000). Quantitative GC/MS analysis was performed with a Varian CP-3800 gas chromatograph (USA) equipped with a VARIAN Saturn 4000 Ion Trap (IT) mass selective detector (USA) and a Saturn GC/IT-MS workstation software version 6.8.…”
Section: Calculation Of Predicted Mixture Effectsmentioning
confidence: 99%
“…Over the last decades, several studies on mixture toxicology have compared two well-established models for the calculation of expected additive mixture effects (Drescher and Boedeker 1995;Payne et al 2000;Rajapakse et al 2001;Silva et al 2002;Pavlaki et al 2011): concentration addition (CA), first defined by Loewe and Muchnik (1926), and independent action (IA) as described by Bliss (1939). The concept of CA is based on the assumption that the mixture constituents have similar modes of action, which means that any component can be replaced partially or totally with another without changing the overall mixture effect.…”
Section: Introductionmentioning
confidence: 99%